Faint galaxies close to QSOs with damped Lyman α absorption systems - Aragón-Salamanca, A; Ellis, R; O'Brien, K (1996)
We have obtained very deep near-infrared images in the fields of 10 QSOs the spectra of which contain damped Lyman α absorption (DLA) systems with 1.7 < zabs < 2.5. The main aim of our investigation is to provide new constraints on the properties of distant galaxies responsible for the DLA absorption. After subtracting the point-spread function associated with the QSO light, we have detected galaxies very close to the QSO line of sight (projected distance 1.2-1.3 arcsec) in two fields. These sources therefore represent promising candidate galaxies responsible for the DLA absorption. Placed at the redshift of the absorber, the impact parameter is 10 h50-1 kpc and the luminosity is close to LK*. Such parameters are consistent with the hypothesis, verified for metallic systems at lower redshift, that slowly evolving massive galaxies produce at least some of the absorption systems of high column density in QSO spectra out to beyond z ≃ 2. In addition to detecting these candidate DLA galaxies, the radio-loud QSOs in our sample show a significant excess of sources on larger scales (θ ≃ 7 arcsec); this excess is not present in the radio-quiet QSO sightlines. We calculate that such an excess could be produced by luminous galaxies in the cores of clusters associated with radio-loud QSOs. Both results confirm that deep imaging of selected QSOs can be a powerful method of finding samples of likely z ≃ 2 galaxies. Follow-up near-infrared spectroscopy is required to secure galaxy redshifts and star formation rates, while deep Hubble Space Telescope (HST) imaging can determine sizes and morphologies, providing valuable information on galaxy properties at large look-back times.